Transparency in Local Government Management: a Study of its Determinants - Ribeiro, Nuno A. (2019)
Transparency of public management is fundamental in bringing citizens closer to public managers, with this being considered universally as an element of good governance. The main aim of this study is to identify the factors determining transparency in public management of Portuguese local authorities. Using the Municipal Transparency Index of 2013 and 2014, socio-demographic, political and economicfinancial variables are studied for the universe of 308 Portuguese local authorities, by testing the previously formulated research hypotheses in the light of agency theory. The results show that transparency in public management of Portuguese local authorities is determined by size, the number of individuals aged between 15 and 74 who use the internet, unemployment rate, financial autonomy and net debt.